Psychometrics of Tourism: A (de)Builder of Quality of Life? Evidence from the Model of Happiness in Dominican Republic - Puig-Cabrera, Miguel (Revista de Estudios Andaluces, 2021)
For small island developing states (SIDS), tourism is often seen as a passport to development and wellbeing. The happiness phenomenon among residents of tourism destinations is usually linked to the concept of quality of life (QoL). The happiness literature suggests that there is a positive correlation between happiness and income of residents in SIDS, but there is not a clear directionality. In this correlation a large impact of non-income factors linked to wellbeing, such as own feelings and attitudes, belonging feeling to a community, identification with cultural and natural heritage, or a fair government that fulfills residents´ needs. Thus, the goal of this research is to uncover the Caribbean model of happiness according to the relationship between tourism and wellbeing in a SIDS. To test this hypothetical-conceptual model of this work, a questionnaire was administered to obtain suitable data for measuring the quality of life based on a total of five constructs and 27 indicators among residents directly involved in the tourism activity. Partial Least Square-Structural Equation Model (PLS-SEM) was the technique used to test this hypothetical conceptual model. This work bring empirical evidence to the happiness literature deepening in the model of wellbeing Dominican Republic characterized by three maxims: 1) the Dominican model of individual happiness is not based on material goods but emotions, and thus, greed is considered a poverty condition among rich people; 2) having more is having more to share with and 3) the public sector continues to be the object of mistrust among Dominican population, without covering their expectations in terms of justice administration or reliability on political leaders, despite perceiving the political environment as stable.